Determinants of job satisfaction amongst employees in the poultry sub-sector of Ghana: a test of equity theory - Oppong Mensah , Nicholas; Christlieb Amrago, Ernest Christlieb; Kofi Asare, Jeffery; Yeboah, Edward; Donkor , Anthony (Applied Studies in Agribusiness and Commerce, 2020)
The study investigated the factors affecting job satisfaction amongst workers of the poultry sub-sector: a test of equity theory in the Dormaa Municipality in the Bono Region of Ghana. The multistage sampling technique was employed in collecting data from 100 poultry workers with the aid of a structured questionnaire. The logit model was employed in modeling the factors affecting job satisfaction. The empirical findings reveal that occupational level, pay, and relationships with co-workers were the statistically significant determinants of job satisfaction. Moreover, the study found that based on equity theory if poultry workers are satisfied with their pay, they would want to stay longer compared to referent others who are not satisfied. Benevolent poultry workers were dominant (52%), followed by equity sensitive (28%) and entitled (20%) poultry workers. Moving forward, the relevance of equity theory on workers in the cocoa value chain should also be investigated as cocoa remains a staple crop in Ghana.JEL Code: Q10